Examining the multidimensional energy poverty trap and its determinants: An empirical analysis at household and community levels in six provinces of China. (October 2022) - Huang, Yatao; Jiao, Wenxian; Wang, Kang; Li, Erling; Yan, Yutong; Chen, Jingyang; Guo, Xuanxuan
Abstract: Modern energy services that are close to perfect are the basis for sustainable development. Measuring energy poverty from a multidimensional perspective and revealing its dynamic evolution has important practical significance for formulating and improving energy policies. After measuring the multidimensional energy poverty index of China's six provinces using data from 2009, 2011, and 2015, this study divided households into three states: non-multidimensional energy poverty, multidimensional energy poverty, and severe multidimensional energy poverty. The stay proportion and migration probability of households in different states were estimated by the mover-stayer model, and their determinants were analyzed at the household and community levels by the hierarchical linear model. The results show that the multidimensional energy poverty of China's six provinces declined. Most households migrated to better states, which indicates that there is no energy poverty trap in China. However, there are risks of returning to poverty in some households. For stayers, the change of their status is formed by the joint action of the household and community, whereas for the movers, it is mainly due to the household conditions. We suggest that, according to the different levels of energy poverty, energy policies should be formulated at different levels and stages. Highlights: Multidimensional energy poverty is a short-term state in China. Household-scale variables dominate the stay and migration of MEP. The role of community-scale variables cannot be ignored. Variables such as the gender of the household head have dual effects on the stay and migration of MEP.